1976
DOI: 10.1016/0072-968x(76)90029-2
|View full text |Cite
|
Sign up to set email alerts
|

Further observations on the anatomy of the ulnar nerve at the wrist

Abstract: A review of the anatomy of the course of the ulnar nerve at the wrist, in the pisohamate tunnel. The exit from this tunnel is the most likely place for compression of the ulnar nerve at the wrist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

1985
1985
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 7 publications
0
9
0
2
Order By: Relevance
“…In a cadaveric and clinical study, McFarlane et al 3 described a specific area in which they observed the nerve to be compressed between the pisohamate ligament and the fibrous arch of the hypothenar muscles, which they referred to as the pisohamate tunnel. This fibrous arch, as described by these authors, is the pisohamate arcade, which is clearly delineated in our study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In a cadaveric and clinical study, McFarlane et al 3 described a specific area in which they observed the nerve to be compressed between the pisohamate ligament and the fibrous arch of the hypothenar muscles, which they referred to as the pisohamate tunnel. This fibrous arch, as described by these authors, is the pisohamate arcade, which is clearly delineated in our study.…”
Section: Discussionmentioning
confidence: 97%
“…It was not until 1965, however, that the term ulnar tunnel syndrome was first introduced by Dupont et al, 2 who described compression of the ulnar nerve in the tunnel by various pathologies, including carpal ganglion and hypertrophy of the palmar carpal ligament. In an effort to better define the compressive anatomy in this region, McFarlane et al 3 identified the pisohamate tunnel, in which compression of the ulnar nerve occurs between the fibrous arch of the hypothenar muscle and the pisohamate ligament. Denman 4 further delineated the pisohamate tunnel as the passage of the deep (motor) branch of the ulnar nerve and suggested the distal portion of the tunnel be referred to as the pisoretinacular space.…”
mentioning
confidence: 99%
“…However, Ombaba et al 1 reported that McFarlane et al 2 described a specific area in which they observed the ulnar nerve to be compressed between the pisohamate ligament and the fibrous arch of the hypothenar muscles, which they referred to as the pisohamate tunnel. Indeed, the region that was called the pisohamate tunnel in the study of McFarlane et al 2 was the equivalent of Guyon's canal.…”
Section: Influence Of Wrist Motion On Its Morphologymentioning
confidence: 97%
“…Guyon's canal has also been termed canalis ulnaris, [1] the distal ulnar tunnel, [2] carpal ulnar neurovascular space, [3] pisoretinacular space, [4] or the pisohamate tunnel. [5] It was first described as a space at the base of the hypothenar eminence by the French surgeon Jean Casimir Felix Guyon in 1861 who became interested in a small protrusion on the palmar aspect of his wrist when he applied pressure to the hypothenar eminence. [6] It was McFarlane who first described it as a tunnel shaped region between the pisohamate ligament and the fibrous arch of the hypothenar muscles.…”
Section: Introductionmentioning
confidence: 99%
“…[6] It was McFarlane who first described it as a tunnel shaped region between the pisohamate ligament and the fibrous arch of the hypothenar muscles. [5,7] The palmar branch representing the continuation of the ulnar nerve passes through Guyon's canal and divides into superficial and deep terminal branches within the canal. The superficial terminal branch supplies the palmaris brevis muscle and the medial palmar skin.…”
Section: Introductionmentioning
confidence: 99%